Does Mandatory Shareholder Voting Prevent Bad Acquisitions? - Becht, Marco; Polo, Andrea; Rossi, Stefano (Review of Financial Studies, 2016)
Can shareholder voting prevent managers from destroying value in corporate acquisitions? Previous studies based on U.S. data are inconclusive because shareholder approval is discretionary. We study the U.K. where approval is mandatory for deals exceeding a multivariate relative-size threshold. We find that in the U.K. shareholders gain 8 cents per dollar at announcement with mandatory voting, or $13.6 billion over 1992-2010 in aggregate; without voting, U.K. shareholders lost $3 billion. U.S. shareholders lost $214 billion in matched deals. Differences-in-differences and multidimensional regression discontinuity analyses support a causal interpretation. Our evidence suggests that mandatory voting imposes a binding constraint on acquirer CEOs.